The expression and regulation of miR-1 in goat skeletal muscle and satellite cell during muscle growth and development. Issue 5 (11th September 2020) - Sui, Menghua; Zheng, Qi; Wu, Hao; Zhu, Lu; Ling, Yinghui; Wang, LiJuan; Fang, Fugui; Liu, Ya; Zhang, Zijun; Chu, Mingxing; Zhang, Yunhai
Abstract: MicroRNA-1 (miR-1) has been shown to play an important role in muscle growth and development, however, it was mainly discovered in model animals. To explore the function and mechanism of miR-1 in goat, we firstly explored the expression profile of miR-1 in goat tissues and cells. Furthermore, the target gene of miR-1 was predicted, and the relationship between miR-1 and one of its target genes, histone deacetylase 4 ( HDAC4 ), was analyzed through double luciferase reporter assay, real-time PCR, and western blot. It was found that the miR-1 is most abundantly expressed in goat heart and skeletal muscle tissue. Meanwhile, the expression of miR-1 showed an increasing tendency from new-born goats to the 7-month-old goats, and then its expression decreases as the goats mature further. In addition, the expression levels of miR-1 decreased in goat skeletal muscle satellite cells with the algebraic increasing of cells. At last, the results showed that HDAC4 is a target gene of miR-1 in goat, and miR-1 can inhibit the post-transcriptional expression of HDAC4, but had no significant influence on the mRNA level of HDAC4 . It was hypothesized that miR-1 promotes muscle development by inhibiting the post-transcriptional expression of HDAC4 in goat.